Seroprotection of Hepatitis B Vaccine in Dental Students Two Decades after Infant Immunization and the Possible Need for Revaccination - Lingawi, Hanadi S.; Afifi, Ibtesam K. (European Journal of Dentistry, 2022)
Objectives This study aimed to assess hepatitis B surface antibody (anti-HBs) persistence among dental students two decades after infant vaccination and immune response after revaccination or booster dose in nonimmune groups.Materials and Methods A cross-sectional study was performed using laboratory reports for anti-HBs performed to dental students at the Umm al-Qura University from 2016 to 2020. Reports were classified according to baseline antibody titer into group I (titer <10 mIU/mL), group II (titer 10 to <100 mIU/mL), and group III (titer ≥100 mIU/mL). The basal antibody titer of each group was correlated to student's gender and birth year and compared with postrevaccination or booster dose titer in groups I and II.Statistical Analysis Data of baseline and postrevaccination anti-HBs antibody titers were analyzed using Statistical Package for Social Science (SPSS). One-way ANOVA was used to compare between different means for antibody titers of students as well as baseline and postrevaccination antibody levels for nonimmune students with nonprotective antibody titers. Pairwise multiple comparison of the difference between baseline and postrevaccination anti-HBs antibody titers were done by post hoc Tukey's honestly significant difference (HSD) test. Chi-squared test was used for comparing between the frequencies. A p-Value of ≤0.05 was considered significant and p < 0.01 was considered highly significant.Results A significant percentage (73.6%) of students had antibody titer <10 mIU/mL, while only 4.8% had antibody titer ≥100 mIU/mL with nonsignificant difference between both genders (χ2 =3.784, p = 0.151). A statistically nonsignificant difference was also found between the three categories of anti-HBs antibody titers among students with different birth dates (χ2 = 13.817, p = 0.182). After revaccination of nonimmune students, 100% of them showed strongly protective antibody titers with mean of 842.88 to 844.58 mIU/mL. A highly significant difference was observed between the mean baseline and postrevaccination antibody titers in both genders, with a higher mean of post revaccination (p = 0.000).Conclusion Two decades after infant immunization, a significant percentage of dental students failed to maintain the anti-HBs seroprotective titer. So titer measurement should be made compulsory before they begin their clinical training and revaccination or booster dose should be given to nonimmune students to maintain a high protection level.
Keywords: hepatitis B; antibody; immunization; dental; vaccine; Saudi Arabia